The Design Posture: A Collaborative Learning-By-Doing Approach - Rita Duina; Marco Berni; Andrea Del Bono (DIID, 2024)
In September 2021, Codesign Toscana1 organised a pop-up school animated by a concept implicitly present in many design-related debates and around which our practices as an interdisciplinary collective have developed over the last five years: the “Design Posture” (hereafter DP). By relying on a collaborative design framework, we experimented with a cooperative learning approach using the urban context as a non-formal education platform and, following the direct experience of the pop-up school, named “Response/Ability” we discuss the possibility of new horizons in the urban context to organize educational platforms that rely on reclaimed city spaces and that generate insights for young generations.